CURRENT ISSUES AND PURPOSE OF TEACHING MATHEMATICS IN SCHOOLS (American Journal of Research in Humanities and Social Sciences, 2022)
In the article, the main task of teaching mathematics in secondary schools and its current issues, the theory of mathematics and related issues, research and mathematical model, methods of teaching mathematics, the concept of teaching method, basic concepts of didactics and methodology, mathematics the practical purpose observed from teaching is described in detail.